The Echo of a Thompson Gun: Folk Music and Left Politics in Ireland and the United States of America, 1951 - 1973 - Sheehan, Jack (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2023)
This thesis explores the link between Irish traditional/folk music and left-wing political organisation in Ireland and the United States of America in the nineteen-fifties, sixties, and seventies. The study begins in 1951 with the visit of American musicologist Alan Lomax to Ireland and ends in 1973 as the Troubles in the North escalated, and Ireland entered the European Economic Community. The thesis explores the growth of a particular left ideology, influenced by currents in both Irish radical Republicanism and the American Old Left, through musical exchange between the two countries. This ideology was self-consciously both traditional and modern, suspicious of the totalising impact of mass Anglo-American culture, and connected Ireland to the decolonizing nations of the world. In doing so, this thesis fills a gap between histories of Republicanism in the mid-century, the role of music in left-wing politics in the United States, transnational studies of ?Irish-America?, and works on the growth and transformation of traditional music in Ireland. The thesis begins with an examination of the role, both real and imagined, that Lomax and his American contemporaries played in the popularisation and revitalisation of Irish music in the nineteen-fifties. Through his interactions with state and semi-state bodies in Ireland and the U.S., this chapter explores the peculiar convergences of ideology between conservatives and leftists on the subject of folk music and culture. Next, the thesis traces the repopularisation of 'rebel' music through the careers of Dominic Behan, and the Clancy Brothers and Tommy Makem. The following chapter studies the fiftieth anniversary commemorations for the 1916 Rising, and their effect on folk music in the following years. This culminates in a discussion of the 'Liberation Fleadh', a music festival held inside the Derry barricades in August 1969. Finally, the thesis explores the role of folk and traditional music in the North during the early years of the Troubles, from 1968 to 1973. Analysing the American civil rights support group, the National Association for Irish Justice/National Association for Irish Freedom, the musical response to the introduction of internment without trial and Paredon Records, a Communist-affiliated label that released Republican music, it explores the role that Irish "rebel" music had as a conduit of political activity, within Ireland and between Ireland and the United States. Finally, it analyses key themes in rebel music in the early Troubles. This thesis situates the folk and rebel music revival in the wider context of global cultural and political exchange.
APPROVED
Keywords: Music; History; Twentieth Century; Nineteen Sixties; Nineteen Ffities; Nineteen Seventies; 1950s; 1960s; 1970s; Fifties; Sixties; Seventies; Political Music; Republicanism; Irish Republicanism; Rebel Music; Rebel Ballads; Ballads; IRA; Official IRA; Left Wing History; Communist History; Communism; Irish Communism; Socialism; Irish Socialism; Troubles; Paramilitarism; Popular Front; Folk Music; American Folk Music; Clancy Brothers; Tommy Makem; Ballad Boom; New York City; Transatlantic; Irish-American; Old Left; Alan Lomax; Tom Clancy; Liam Clancy; Paddy Clancy; The Dubliners; EEC; Behan; Dominic Behan; Eamonn McCann; Mick Moloney; Barbara Dane; RT?; SNCC; PIRA; Radio Eireann; People's Democracy; NAIJ; NAIF; INAC; INLA; CPUSA; CPI; CC?; Comhaltas Ceolt?ir? ?ireann; Men Behind the Wire; Liberation Fleadh; Fleadh; Freedom Fleadh; Derry; 1966; 1916 Rising; Folk Revival